Collaborating towards coherence : lexical cohesion in English discourse - Tanskanen, Sanna-Kaisa (Pragmatics & beyond, 2006)
This book approaches cohesion and coherence from a perspective of interaction and collaboration. After a detailed account of various models of cohesion and coherence, the book suggests that it is fruitful to regard cohesion as contributing to coherence, as a strategy used by communicators to help their fellow communicators create coherence from a text. Throughout the book, the context-sensitive and discourse-specific nature of cohesion is stressed: cohesive relations are created and interpreted in particular texts in particular contexts. By investigating the use of cohesion in four different t.